Economic and Clinical Outcomes of Pediatric Patients Under Two With Respiratory Syncytial Virus Infection in Thailand: A Real-world Retrospective Cohort Study - Tan C.J. (2023)
BACKGROUND: Respiratory syncytial virus (RSV) is a common cause of acute respiratory tract infection in children, including in Thailand. We conducted this study to evaluate the economic and clinical outcomes of patients <2 years old with RSV infection at a tertiary teaching hospital in Thailand. METHODS: This was a retrospective cohort study during 2014-2021. To be eligible, patients had to report at least 1 positive RSV test and were <2 years old. Descriptive statistics were used to describe baseline characteristics, healthcare resource utilization, direct medical costs (1 US dollars [USD] = 31.98 Thai Baht) and clinical outcomes. RESULTS: Among 1370 RSV-positive patients, 49.9% of the patients (n = 683) were hospitalized at or within 3 days of RSV diagnosis with a median length of stay of 6 days (interquartile range [IQR]: 4-9 days), 38.8% were diagnosed with RSV-related respiratory complications (n = 532) and 1.5% died during the hospitalization episode (n = 20). A total of 22.5% of hospitalized patients (n = 154) received critical care during the hospitalization episode. The median cost of each RSV episode was USD539 (IQR: USD167-USD2106) and was higher among hospitalized patients (median: USD2112; IQR: USD1379-USD3182) compared with nonhospitalized patients (median: USD167; IQR: USD112-USD276). CONCLUSIONS: RSV infection represents a potentially important contributor to healthcare resource use and medical costs among children <2 years old in Thailand. Coupled with epidemiologic data, findings from our study will be useful to illustrate the overall economic burden associated with RSV infection among children in Thailand.